Emerging Role of PPAR-β/δ in Inflammatory Process Associated to Experimental Periodontitis - Rosanna Di Paola; Francesco Briguglio; Irene Paterniti; Emanuela Mazzon; Giacomo Oteri; David Militi; Giancarlo Cordasco; Salvatore Cuzzocrea (Mediators of Inflammation)
The aim of the present study was to evaluate the contribution of peroxisome proliferator-activated receptor (PPAR-β/δ) in animal model of periodontitis. Male Sprague-Dawley rats were lightly anaesthetized with pentobarbitone (35 mg/kg). Sterile, 2-0 black braided silk thread was placed around the cervix of the lower left first molar and knotted medially. Animals received GW0742 (0.3 mg/kg, 10% DMSO, i.p. after the ligature placement and daily for eight days). At day 8, the gingivomucosal tissue encircling the mandibular first molar was removed. One the eighth day after placement of the ligature, we evaluated (1) NF-κB expression, (2) cytokines expression, (3) iNOS expression, (5) the nitration of tyrosine, (6) apoptosis, and (8) the degree of gingivomucosal tissues injury. Administration of GW0742 significantly decreased all of the parameters of inflammation as described above. Taken together, these results demonstrate that GW0742 exerts an anti-inflammatory role during experimental periodontitis and is able to ameliorate the tissue damage.